Menakar Kesiapan SDM Syariah - Sudirman Teba (Unisia, 2003)
The rapid development of Islamic Banking system in Indonesia is adorable. No more than 11 years since the regulation on banking in 1992, there are some big banks has open its Syariah bank windows. Accountless smaller Islamic banks are in operation. However, some serious problems must be inevitably solved soon, i.e., the problem on the provision of human resources. Faculty of Syariah, which is used to accustomed only to the classical fiqh need be reformed in the new curriculum and educational system. Similarly, graduant of faculties of Economics, need to hard work to understand the basis of Syariah Islamiyah in term of banking rather than conventional banking system. If the provision for such human resources fails, it will be embarrassing for Moslem society in the country because of inability to provide professional human resources.